(untitled) (GESTIÓN Y TENDENCIAS, 2024)
With the aim of exploring continuity between the mathematics of education and the mathematics of professional practice, this paper studies mathematical modeling from a socio-epistemological standpoint. This type of modeling focuses on the practices of professional communities, which involve the recurrent and shared activity of their members. This view acknowledges the complexity and dynamism of modeling practices, which are rooted in a variety of professional and non-professional communities. Carrying out such professional practices in the classroom with students in training contributes to the early shaping of their professional identity.